2001
DOI: 10.1139/v01-086
|View full text |Cite
|
Sign up to set email alerts
|

Using secondary alpha deuterium kinetic isotope effects to determine the stereochemistry of an E2 reaction; the stereochemistry of the E2 reaction of 1-chloro-2-phenylethane with potassium tert-butoxide in tert-butyl alcohol

Abstract: Isotopic labelling studies have shown that the E2 reaction of 1-chloro-2-phenylethane with potassium tert-butoxide in tert-butyl alcohol occurs via an anti-periplanar stereochemistry. This demonstrates that the different secondary alpha deuterium kinetic isotope effects found for the high and low base concentrations and in the presence of 18-crown-6 ether are because of changes in transition state structure that occur when the form of the reacting base changes rather than to a change in the stereochemistry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…cis-1,2-Dideuteriostyene ( 1a ) was prepared by treating phenylacetylene with Cp 2 ZrDCl, followed by D 2 O, according to a procedure by Bercaw et al 1 H NMR spectroscopy indicated 93% deuterium incorporation, in accord with reported spectral data . The product was stored at −20 °C and used within 12 h of isolation.…”
Section: Methodsmentioning
confidence: 96%
“…cis-1,2-Dideuteriostyene ( 1a ) was prepared by treating phenylacetylene with Cp 2 ZrDCl, followed by D 2 O, according to a procedure by Bercaw et al 1 H NMR spectroscopy indicated 93% deuterium incorporation, in accord with reported spectral data . The product was stored at −20 °C and used within 12 h of isolation.…”
Section: Methodsmentioning
confidence: 96%
“…It is worth noting that this type of catalysis to a chloride ion leaving group using hydrogen bonding to protic solvents in S N reactions has been suggested by Thornton and Gajewski. 20,21 Electophilic catalysis for the removal of a chloride ion leaving group by metal ions in E2 elimination reactions of alkyl chlorides was suggested by Smith et al 22 and by Zavada and co-workers. 23,24 If this type of catalysis occurred, it would stabilize the developing chloride ion making it a better leaving group.…”
Section: Resultsmentioning
confidence: 99%